Pengaruh Corporate Social Responsibility terhadap Kinerja Keuangan melalui Rasio Profitabilitas dan Solvabilitas pada PT Indofarma Tbk (2020–2024) - Nandita Aurina Agustin; Asep Muslihat; Nana Diana (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
This study examines the relationship between Corporate Social Responsibility (CSR) implementation and financial performance at PT Indofarma Tbk during the 2020-2024 period. The background to this research stems from the growing awareness of the importance of corporate social and environmental responsibility in conducting business activities, particularly for companies operating in the pharmaceutical industry. The literature review is based on the concept of CSR as a form of a company's ethical commitment to society and the environment, as well as the concept of financial performance as measured by Return on Assets (ROA), Return on Equity (ROE), and Debt to Equity Ratio (DER). This study employed a mixed methods approach: a qualitative descriptive approach through analysis of sustainability reports and company annual reports, and a quantitative approach through analysis of company financial report data during the study period.